2021
DOI: 10.3390/catal11020235
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of N/Zr Co-Doped TiO2 for Photocatalytic Degradation of p-Nitrophenol in Wastewater

Abstract: TiO2 prepared by a green aqueous sol–gel peptization process is co-doped with nitrogen and zirconium to improve and extend its photoactivity to the visible region. Two nitrogen precursors are used: urea and triethylamine; zirconium (IV) tert-butoxide is added as a source of zirconia. The N/Ti molar ratio is fixed regardless of the chosen nitrogen precursor while the quantity of zirconia is set to 0.7, 1.4, 2, or 2.8 mol%. The performance and physico-chemical properties of these materials are compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Increasing the Zr 4+ content in the material up to 3.7% caused V p ’s increase, and then drop when Zr 4+ content reaches 5.6%, while S p grew from 3.8 to 7.5 nm. The above observations may be concluded that prepared materials have mesoporous structures created by aggregates built of spherical TiO 2 nanoparticles [ 74 ]. Undoubtedly, the structure of used precursors (isopropoxide and n-propoxide alkoxy chains) can act as semi-templates and induce pores’ growth in investigated materials [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the Zr 4+ content in the material up to 3.7% caused V p ’s increase, and then drop when Zr 4+ content reaches 5.6%, while S p grew from 3.8 to 7.5 nm. The above observations may be concluded that prepared materials have mesoporous structures created by aggregates built of spherical TiO 2 nanoparticles [ 74 ]. Undoubtedly, the structure of used precursors (isopropoxide and n-propoxide alkoxy chains) can act as semi-templates and induce pores’ growth in investigated materials [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the contribution of Benkhennouche-Bouchene et al [4], TiO 2 that was prepared using a green aqueous sol-gel peptization process was co-doped with nitrogen and zirconium to improve and extend its photoactivity to the visible region. For all doped and co-doped samples, TiO 2 nanoparticles with sizes ranging from 4 to 8 nm were formed of anatase-brookite phases.…”
Section: Tio 2 -Based Photocatalystsmentioning
confidence: 99%
“…To the best of our knowledge, there is no previous research on the photocatalytic degradation of PAHs in tobacco tar. Thus, we compared our optimal sample (over 96% degradation in 50 min) with that for PAH removal in water treatment, such as TiO 2 (over 99% in 24 h) [49], ZnO/TiO 2 (98% in 2 h) [50], TiO 2 (over 66% in 39 min) [51], Evonik P25 (70% in 8 h) [52] and Pr/TiO 2 (over 99% in 3 h) [53]. To investigate the photodegradation process, electron paramagnetic resonance (EPR) spectra were employed to confirm the generated reactive radicals under simulated solar light.…”
Section: Activity For Photodegradation Of Pahs From Tobacco Tarmentioning
confidence: 99%